Reductive Debromination of Polybrominated Diphenyl Ethers - Microbes, Processes and Dehalogenases - Zhao, Siyan; Rogers, Matthew J.; Ding, Chang; He, Jianzhong (Frontiers in Microbiology, 2018)
Extensive utilization of polybrominated diphenyl ethers (PBDEs) as flame retardants since the 1960s in a variety of commercial products has resulted in ubiquitous environmental distribution of commercial PBDE mixtures. Dangers posed to biological populations became apparent after the discovery of elevated levels of PBDEs in biota, most notably in human breast milk and tissues. Environmental persistence of PBDEs results in significant transboundary displacement, threatening fragile ecosystems globally. Despite efforts to curtail usage of PBDEs, public concern remains about the effects of legacy PBDEs contamination and continued discharge of PBDEs in regions lacking restrictions on usage and manufacture. Among available technologies for remediation of PBDEs such as ex situ soil washing, electrokinetic degradation, and biodegradation, this review focuses on bioremediation by microbes under anaerobic conditions. Bioremediation is generally preferred as it is less disruptive to contaminated ecosystems, is cost-effective, and can be implemented at sites that may be inaccessible to more traditional ex situ methods. The aims of this review are to 1) summarize current knowledge of anaerobic microbes that debrominate PBDEs and their associated synergistic partnerships with non-dehalogenating microbes; 2) explore current understandings of the metabolic reductive debromination of PBDE congeners; 3) discuss recent discoveries on dehalogenase genes involved in debromination of PBDEs.